Prevalence of etiologic agents causing invasive bacterial disease and evaluation of their antibiotic susceptibility pattern - Rahman, Md Mijanur; Uddin, Mohammad Sharif; Aktar, Salma; Ali, Mohammad Shaokat; Paul, Partha; Hasan, Md Mahmudul; Rahman, Shah Md Ataur (Asian Journal of Medical and Biological Research, 2018)
Invasive bacterial diseases (IBD) cause significant morbidity and mortality which leads to enormous health suffering and economic frustration in Bangladesh especially in people with resource poor region. The prevalence of IBD may vary even in different regions in a country. To understand the prevalence of etiologic agents causing IBD and determining their response to commonly used standard antibiotics we conducted a retrospective cross sectional study in rural town of Bangladesh on patient attended for blood culture with IBD sign-symptoms in well reputed microbiology lab. We considered IBD patients (118) of all age groups (0-85 years) both gender (male 54% and female 46%). 25% (30) blood culture of all IBD patients found bacterial growth positive including contaminant Staphylococcus sp. (10). The isolated IBD etiologic agents are S. aureus (10), Salmonella sp. (5), Salmonella Paratyphi (1), E. coli (2), Shigella sp. (1), Pseudomonas sp. (1). We could have retrieved antibiotic susceptibility testing data of five isolates including S. aureus (1), Salmonella sp. (2), Salmonella Paratyphi (1), Pseudomonas sp. (1); which showed except Salmonella sp. all isolates are sensitive to tested commonly used standard antibiotics. Two non typhoidal Salmonella sp. showed intermediate sensitivity to ciprofloxacin (5 ìg) which indicate reconsideration of choosing non typhoidal Salomonella sp. infection with ciprofloxacin (5 ìg). As it is a retrospective, not well organized cross sectional study; these findings may not represent the entire actual scenario of IBD in the region. As a consequence, a well organizing and adequately powered study must need to be conducted Asian J. Med. Biol. Res. December 2018, 4(4): 330-336